STRATEGI VISUAL KARAKTER ABID DAN DINA PENDIDIKAN KARAKTER SDII AL ABIDIN SURAKARTA - Evelyne Henny Lukitasari; Satriya Adhi (Canthing, 2022)
Character education prioritizes the formation of students' character which refers to the multiple intelligent method or multiple intelligences. A multiple intelligence is not only seen from one's logical intelligence, but also intelligence in having the ability to solve problems, character education aims at inculcating knowledge, love, sensitivity, discipline awareness, independence and creativity in children, which is to promote the cultivation of noble character in oneself. protege. SDII Al Abidin Surakarta applies a character education curriculum in its teaching and learning process. Elementary school age has sensitivity in receiving information in visual form. Especially visuals in the form of figures, so that in introducing and familiarizing students at SDII Al Abidin Surakarta, they need figures. Figures that represent the character of the students of SDII Al Abidin Surakarta. Based on this, it is necessary to research on the elements forming the character figure of SDII Al Abidin Surakarta character education by using qualitative research methods with data collection techniques by means of interviews.